Estados hipercoagulables primario y deficiencia de proteínas "C" y "S". Reporte de un caso y revisión de la literatura. - Paez M., Luis; Chaparro L., Aída (Revista Médica Herediana, 2013)
We present a patient with upper gastrointestinal bleeding and gastric varices due to mesenteric and splenic thrombosis related with a hypercoagulable state secondary to protein C and proteins S deficiency. We also did a review of the literature about deficiency of these proteins and their importance as a cause of venous thrombosis not well recognize yet. KEY WORDS: Protein C, Protein S, hypercoagulable state, venous thrombosis, upper gastrointestinal bleeding.